Possibilities of using design thinking to improve the process of medical care - A. N. Popsuyko; Ya. V. Danilchenko; E. A. Batsina; D. V. Kilizhekova; D. V. Karas; G. V. Artamonova (Исследования и практика в медицине, 2022)
Purpose of the study. To describe the theoretical foundations and practical application of design thinking technology in the activities of a medical organization as a tool for managing interaction with patients to improve the provision of medical care for cardiovascular diseases.Materials and methods. The work was carried out on the basis of the Research Institute for Complex Issues of Cardiovascular Diseases (Kemerovo). When using methods of sociological research (questioning, content analysis). In the period from 2015 to 2020, 43865 patients were treated at the institution, of which 16886 were questioned. The analysis of domestic and foreign literature, as well as regulatory documents was carried out for the period from 2015 to 2020 using the keywords: "design thinking", "Service design", "design thinking in medicine."Results. The possibility of adapting the technology of design thinking to medical and diagnostic activities in research institutes, namely to the process of assessing patient satisfaction, is shown. Due to the presence of an effective mechanism for managing interaction with patients, in the research institute in the period from 2011 to 2020, there was a decrease in justified complaints (more than 2 times), and the level of patient satisfaction reaches target values.Conclusion. Design Thinking is part of the patient management process as an initial step in assessing patient satisfaction. The described technology can be used by any medical organization.